2012
DOI: 10.1159/000336603
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Aerobic Fitness and Lifestyle Characteristics in Preschoolers according to their Weight Status and Sports Club Participation

Abstract: Objective: This study assesses differences in adiposity, aerobic fitness, and lifestyle characteristics in preschoolers according to their weight status and sports club (SC) participation. Method: As part of the Ballabeina study, 600 randomly selected preschoolers (mean age 5.1 ± 0.6 years; 50.2% girls) were analyzed. Body composition was measured by bioelectrical impedance, aerobic fitness by the 20-meter shuttle run test, and physical activity by accelerometers. Eating habits, media use, and SC participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 70 publications
3
25
1
Order By: Relevance
“…Further, only participation in organized sports was considered rather than total physical activity, which may be problematic, especially in younger children. Ebenegger et al [60], however, did show a direct relationship between sports participation and habitual PA in preschoolers. The large sample size, on the other hand, is a strength of the present study, and an analysis of missing value did not show any systematic bias.…”
Section: Discussionmentioning
confidence: 94%
“…Further, only participation in organized sports was considered rather than total physical activity, which may be problematic, especially in younger children. Ebenegger et al [60], however, did show a direct relationship between sports participation and habitual PA in preschoolers. The large sample size, on the other hand, is a strength of the present study, and an analysis of missing value did not show any systematic bias.…”
Section: Discussionmentioning
confidence: 94%
“…These findings are supported by previous studies. 24 On the other hand, using questionnaire and heart rate monitoring, Deflandre et al 25 observed 80 schoolchildren showing that the most sportinvolved children are not necessarily the most active ones. However, in their study, it has been suggested that children with excess body weight are more likely to hesitate to undertake sports activities which supports the findings of overweight and obese children being less likely to engage in organized sports.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the reliability of the fitness tests used for the Ballabeina study conducted in Swiss preschool children is reported in several articles [15][16][17][18][19][20], but only one article representing this project is included in the present review [19]. Although inclusion of information on reliability, validity or the relationship with health outcomes of field-based physical fitness tests was a criterion for final inclusion of a study in the review, these terms were not entered in the electronic search and the authors conducted the selection manually.…”
Section: Only One Original Article Per Study Includedmentioning
confidence: 99%